Dispersal and recruitment of fish in an intermittent stream network. (24th June 2013) - Dexter, Tim; Bond, Nick; Hale, Robin; Reich, Paul
Abstract Animal movement is an important process connecting habitats in heterogeneous landscapes, and can play a key role in population persistence. Laboratory swim trials were conducted to determine and compare the dispersal capabilities of two native Australian fish, mountain galaxias (Galaxias olidus, Family Galaxiidae) and southern pygmy perch (Nannoperca australis, Family Nannopercidae) that maintain populations in hydrologically variable and intermittently flowing streams in south‐eastern Australia. These experiments showed that G. olidus had significantly greater swimming endurance under a range of flow velocities. Concurrent field surveys were used to establish whether swimming abilities observed in laboratory studies were consistent with patterns of inferred movement from distribution and abundance patterns observed in the field. Data collected at multiple sites from headwater to lowland reaches along multiple streams revealed substantial temporal changes in the distribution of young‐of‐year (0+) G. olidus, with spawning occurring at upland sites in winter, followed by downstream larval migration and subsequent upstream movement in late spring. Observed spatial and temporal patterns in G. olidus abundances were consistent with a source‐sink population structure, which may be disrupted by prolonged cease‐to‐flow periods during drought years. In contrast, results for N. australis suggested limited dispersal, with restricted local populations that persist at sites with permanent surface water. These field and laboratory findings complement our understanding of the spatial population structure of these two species in intermittent streams, and highlight the importance of understanding the role of dispersal in species conservation and habitat restoration.